The transfer of international technology : (Edward Elgar Publishing, 1992)
This book focuses on particular technologies whilst examining aspects of the dimensions of transfer: obstacles, vehicles, circumstances of adoption, modification, reverse flows. The cases include motor vehicles, heavy chemicals, synthetic rubber, petroleum, computers and textiles. Of special interest are the studies of technologies exported from Japan to her neighbours and to the West. The book makes an important contribution to the study of international technology transfer in the twentieth century